The Impact of Authentic Leadership on Personal Performance of Employees with Regard to Job Characteristics and Emotional Commitments - Mehrzad Abdollahzadeh; minoo yousefi (Allameh Tabataba'i University Press, 2022)
The purpose of this study was to investigate the effect of authentic leadership on individual performance with respect to job characteristics and emotional commitments of staff in the education department of Guilan province. The research is applied in terms of purpose and descriptive. The statistical population of the study is the staff of the Guilan Education Organization, which was selected as a sample by cluster sampling method based on Cochran's formula. The data collection tool was a questionnaire that was used to measure authentic leadership from Avolio et al. (2007), Moody et al. (1990), Hockman & Oldham (1975), Job Performance of Staple et al. (1999). In order to analyze the data, the structural equation modeling method based on the partial least squares approach was used by Smart PLS3 statistical software. Findings showed that authentic leadership has a significant effect on emotional commitment and individual performance of employees of the Guilan Education Organization. The effect of emotional commitment on the individual performance of the staff of the Guilan Education Organization was also confirmed. It was also found that emotional commitment has a mediating role in the impact of authentic leadership on individual performance of employees and the moderating role of job characteristics variable in the impact of authentic leadership on individual performance of employees of Guilan Education Organization was also confirmed.